The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ijc.32917
|View full text |Cite
|
Sign up to set email alerts
|

End of an era for erythropoiesis‐stimulating agents in oncology

Abstract: Erythropoiesis‐stimulating agents (ESAs) are available to treat chemotherapy‐induced anemia (CIA). In 2007–2008, regulatory notifications advised of venous thromboembolism and mortality risks while the Center for Medicare and Medicaid Services' restricted ESA initiation to patients with hemoglobin <10 g/dl. In 2010, a Risk Evaluation and Mitigation Strategies required consent prior to administration. We evaluated ESA utilization from 2003 to 2012 and obtained private health insurer claims data for persons with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
4
1
1
Order By: Relevance
“…Our study contradicts with results from a study by Schoen et al that uses the IMS LifeLink™ Health Plan Claims Database, which is composed of commercial health plan information [56]. They found that odds of receiving epoetin decreased after risk communications and REMS, but initially increased for darbepoetin after box warnings were disseminated.…”
Section: Plos Onecontrasting
confidence: 99%
“…Our study contradicts with results from a study by Schoen et al that uses the IMS LifeLink™ Health Plan Claims Database, which is composed of commercial health plan information [56]. They found that odds of receiving epoetin decreased after risk communications and REMS, but initially increased for darbepoetin after box warnings were disseminated.…”
Section: Plos Onecontrasting
confidence: 99%
“…Table 4 summarizes the most common complications observed with these therapeutic modalities and the current standards for their management. 90,91,110,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] Targeted Therapeutic-Related Complications Targeted therapies represent the subclass of antineoplastic agents deliberately engineered to interfere with oncogenic signal transduction pathways and are divided into smallmolecule inhibitors, monoclonal antibody-based pharmaceuticals, and cell-based agents. In general, targeted agents are less toxic than nonspecific cytotoxic chemotherapeutics; however, because many agents require long-term use, both acute and chronic treatment-related toxicities should be considered (Fig.…”
Section: Table 3 (Continued)mentioning
confidence: 99%
“…• Erythropoiesis-stimulating agents are no longer indicated for cancer-related anemia (Schoen 2020 123 ).…”
Section: Syndrome Presentation Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…ЭПО способствует образованию эритроцитов из частично детерминированных клеток -предшественников эритропоэза. Профиль его побочных эффектов включает не только АГ, которая встречается практически у 35% пациентов, но и тромбоэмболические осложнения, ограничивающие применение препарата [47,48]. АГ обычно фиксируется через 2-16 недель после начала применения ЭПО [49].…”
unclassified